Internalization Of Islamic Religious Values In Building Religious Character Of Students At Ma Al-Mahrusiyah Lirboyo - khodijah; Dedi Setiawan; M. Sayyidul Abrori (Journal of Research in Islamic Education, 2022)
This article is focused on knowing the internalization of Islamic religious values ​​in building the religious character of students at MA Al-Mahrusiyah Lirboyo. This is done because religious education carried out in schools has not been fully successful. Therefore this research is important to do in shaping students' religious character. This research is a descriptive qualitative research conducted at MA Al-Mahsuriyah Lirboyo. The subjects of this research are teachers and students. Techniques for collecting data that are used namely observation, interviews and documentation. Techniques for data analysis include data reduction, data presentation, drawing conclusions. Then checking the validity of the data is carried out using the triangulation technique. The results of the study show that the internalization of Islamic religious values ​​in building the religious character of students at MA Al-Mahsuriyah Lirboyo runs in an orderly and orderly manner, because the students are quite active and enthusiastic in carrying it out. In order to achieve a better result a strategy is needed that supports, among them through the method of giving by example (exemplary), religious lectures, advice and punishment which must be carried out continuously and adapted to the values ​​to be conveyed.